Edukasi Kewirausahaan dalam Meningkatkan Minat Berwirausaha di Kalangan Guru Sekolah Minggu Gereja Batak Karo Protestan (GBKP) Klasis Medan Kampung Lalang - Veramika Sembiring; Erni Dewi Munthe; Lennaria L Tarigan; Daniel P Bangun (ULINA: Jurnal Pengabdian kepada Masyarakat, 2026)
This Community Service Program (PKM) aims to increase entrepreneurial interest among Sunday School teachers of the Gereja Batak Karo Protestan (GBKP) Klasis Medan Kampung Lalang through entrepreneurship education. The program was conducted on 15 March 2026 using lectures, discussions, and simple business simulations. A total of 45 participants were involved, with 27 respondents completing pre-test and post-test evaluations. Results show a significant increase in entrepreneurial knowledge, opportunity recognition, and motivation, with average scores improving from a low category (2.00–2.30) to a high category (4.00–4.30). The program concludes that entrepreneurship education effectively enhances entrepreneurial interest.